2015
DOI: 10.1039/c4ra11779d
|View full text |Cite
|
Sign up to set email alerts
|

A new high sensitivity Na2LiPO4:Eu OSL phosphor

Abstract: A new high sensitivity Na2LiPO4:Eu optically stimulated luminescence dosimeter (OSLD) material was prepared by a simple solid-state diffusion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…It can be seen from Figure 6 that for the microcrystalline particles (size range 250 µm-43 µm) the dose response is almost linear up to 1.0 kGy and start saturating thereafter. It is similar to the results already reported in our literature [13]. The main difference is that the sensitivity of the phosphor material decreases with the particle size as expected.…”
Section: Sensitivity and Dose Responsesupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen from Figure 6 that for the microcrystalline particles (size range 250 µm-43 µm) the dose response is almost linear up to 1.0 kGy and start saturating thereafter. It is similar to the results already reported in our literature [13]. The main difference is that the sensitivity of the phosphor material decreases with the particle size as expected.…”
Section: Sensitivity and Dose Responsesupporting
confidence: 92%
“…BeO need to take specially because its dust is very toxic and its inhaling could lung deceases called berylliosis. TL/OSL highly sensitive phosphors, are investigated as NaMgF 3 :Eu 2+ [5], NaLi 2 PO 4 :Eu [12], NaLi 2 PO 4 :Ce [10], SiO 2 :Cu [2], LiMgPO 4 :Tb,B [4], Y 3 Al 5 O 12 :C [6], Na 2 SiF 6 :Cu,P [1], Al 2 O 3 :B [14], LiAlO 2 [7], MgO:Tb [3]. However, most of them suffered with their limitations like low sensitivity, high fading, reusability issues, low dose saturation and complicated TL glow curves.…”
Section: Introductionmentioning
confidence: 99%
“…In situ cooling of the mixture up to 573 K was achieved by keeping it in the furnace for about 20 minutes aer switching off the furnace as per the suggestion prescribed by other workers. 18 Aer this, the powder was taken out from the furnace and was kept on an alumina plate at room temperature. The powder and pellet form of the same mixture was used for further studies.…”
Section: Materials Synthesismentioning
confidence: 99%
“…[2][3][4]. It has been found that some thermoluminescence dosimeter (TLD) materials may change their thermoluminescence (TL) characteristics on annealing at different temperatures and/or on heating and cooling several times during readouts for its reuse and could lose their reusability [5]. There is decrease in the efficiency of luminescence due to this which is generally termed as thermal quenching [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since last one decade many researchers have synthesized and studied a range of materials as OSL phosphors, such as, NaLi2PO4:Eu [5], MgO:Tb [9], NaMgF3:Eu 2+ [10], Y3Al5O12:C [11], Al2O3:B [12], LiMgPO4:Tb, B [13], LiAlO2 [14], K2Ca2(SO4)3:Cu [15], Na2SiF6:Cu,P [16], NaLi2PO4:Ce 3+ [17]. However, no phosphor could find sensitivity comparable to Al2O3:C (commercially available α-Al2O3:C of Landauer Inc.).…”
Section: Introductionmentioning
confidence: 99%